Perbandingan Aktivitas Antioksidan Sediaan Wardah Aloe vera dan Nature Republic Aloe vera 92% - Fitri Volorida Hutabarat (Program Studi S1 Farmasi, STIKES Senior, Medan, 2023)
Antioxidants are compounds that have been developed in the health and food fields, such as food preservatives and as treatments that are triggered by free radicals. The aim of this study was to determine and compare the antioxidant potential of Wardah aloe vera and Nature Republic aloe vera 92%. The research method used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method with a UV-Vis spectrophotometer at a wavelength of 517 nm. Antioxidant activity test of Wardah aloe vera and Nature Republic aloe vera 92% preparations at concentrations of 50 µg/ml, 100 µg/ml, 150 µg/ml, 200 µg/ml. Vitamin C at a concentration of 2.5 µg/ml, 5 µg/ml, 10 µg/ml, 15 µg/ml as a positive control. The IC50 value for the Wardah aloe vera preparation was 199.207 µg/ml, Nature Republic aloe vera 92% was 185.641 µg/ml. The IC50 value of Vitamin C is very strong, namely 16.9235 µg/ml. The conclusion is that the preparations of Wardah aloe vera and Nature Republic aloe vera 92% have moderate antioxidant activity.